2002
DOI: 10.1123/japa.10.3.290
|View full text |Cite
|
Sign up to set email alerts
|

Muscle Adaptations to 7 Days of Exercise in Young and Older Humans: Eccentric Overload versus Standard Resistive Training

Abstract: This study compared muscle adaptations after 7 days of exercise with eccentric-overload (EO) or standard (ST) resistive training in young (20 years) and older (69 years) adults. Young EO and ST gained 103 and 30 N, respectively, and older EO and ST gained 63 and 25 N of strength, respectively (all p < .05). Types I and IIa MHC mRNA levels were not altered, but Type IIx levels decreased 31% and 63% after the first and seventh exercise bouts, respectively, in young and decreased 30% after the seventh bout in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…Further, there was no differential effect of RENEW or TRAD on the number of days high fall risk older adults survived without a fall or a near-fall event. These results were not expected since earlier findings with mobility-limited [ 16 , 18 , 19 ], frail [ 15 ] and generally healthy [ 39 , 40 ] older adults engaging in eccentric resistance exercise of the lower extremities for 10–12 weeks have previously demonstrated improved mobility and muscle responses that exceeded those stemming from more traditional-types of resistance exercise regimens. Two defining properties of eccentric muscle contractions, i.e., the force production potential being uniquely high yet the energy cost to produce this force being uniquely low [ 41 – 43 ], are thought to underlie these previous RENEW effects.…”
Section: Discussionmentioning
confidence: 67%
“…Further, there was no differential effect of RENEW or TRAD on the number of days high fall risk older adults survived without a fall or a near-fall event. These results were not expected since earlier findings with mobility-limited [ 16 , 18 , 19 ], frail [ 15 ] and generally healthy [ 39 , 40 ] older adults engaging in eccentric resistance exercise of the lower extremities for 10–12 weeks have previously demonstrated improved mobility and muscle responses that exceeded those stemming from more traditional-types of resistance exercise regimens. Two defining properties of eccentric muscle contractions, i.e., the force production potential being uniquely high yet the energy cost to produce this force being uniquely low [ 41 – 43 ], are thought to underlie these previous RENEW effects.…”
Section: Discussionmentioning
confidence: 67%
“…27,28,39,40 Todavia, a pesquisa de Hortobágyi et al 41 utilizou o teste de 3-RM com a referida população, alegando que os idosos o toleram melhor devido à menor carga suportada, contrapondo o método utilizado por este estudo.…”
Section: 31unclassified
“…Portanto, os ganhos de força apresentados nesta pesquisa corroboram outros estudos. 27,33,41,[45][46][47] …”
Section: 31unclassified
“…Many research studies with a varied number of participants of diverse backgrounds (healthy older individuals and older individuals with health problems or other limitations) have demonstrated the successful and safe performance eccentric training with continuously increasing intensity and volume over time [ 19 , 20 , 21 , 52 , 58 , 61 , 63 , 64 , 65 , 66 , 70 , 71 , 72 , 73 , 74 , 75 ]. For instance, in the Ploutz and Snyder’s [ 70 ] study, healthy older women performed eccentric training for a duration of 12 weeks with no reported injuries emerging from the experimental stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the Ploutz and Snyder’s [ 70 ] study, healthy older women performed eccentric training for a duration of 12 weeks with no reported injuries emerging from the experimental stimuli. Hortobágyi et al [ 71 ] performed a 7 day eccentric overload study including older women, and they reported no injury or dropout as a result of the study protocol. Reeves et al [ 58 ] examined a 14 week adaptation to eccentric training in old men and women and did not report injury emerging from the study protocol.…”
Section: Introductionmentioning
confidence: 99%